Ionically conducting and photoresponsive liquid crystalline terpolymers: Towards multifunctional polymer electrolytes. (December 2018) - Vanti, Laura; Mohd Alauddin, Sakinah; Zaton, Daniel; Aripin, Nurul Fadhilah Kamalul; Giacinti-Baschetti, Marco; Imrie, Corrie T.; Ribes-Greus, Amparo; Martinez-Felipe, Alfonso
Graphical abstract: Highlights: New side-chain terpolymers contain mesogenic, light-responsive and polar groups. Terpolymers show liquid crystal smectic behaviour in a broad range of compositions. Polar groups confined between smectic layers can act as anisotropic ionic pathways. Balanced compositions of the monomers promote liquid crystallinity and conductivity. Terpolymers show signs of ionic mobility decoupled from polymer segmental motions. Abstract: We have prepared a series of new ionically conducting polymer electrolytes consisting of side-chain liquid crystal terpolymers with mesogenic azobenzenes, sulfonic acid groups and methyl methacrylate. The poly[10-(4-methoxyazobenzene -4′-oxy)decyl methacrylate]-co-poly[2-acrylamido-2-methyl-1-propanesulfonic acid]-co-poly[methyl methacrylate]s, 10-MeOAzB/AMPS/MMA terpolymers, were synthesised by a one-pot conventional radical polymerisation. All samples were characterised by NMR, GPC/SEC, FT-IR, POM, XRD, DSC, UV–visible spectrophotometry and EIS. The terpolymers have light responsive properties, and exhibit liquid crystallinity over a wide range of compositions. Above a certain threshold of AMPS content, the 10-MeOAzB/AMPS/MMA terpolymers exhibit ionic conductivities in the 10 −8 –10 −4  S·cm −1 range, with signs of decoupling of ionic mobility from segmental motions of the polymer.